Abnormal cortical thickening and thinning in idiopathic normal-pressure hydrocephalus - Kang, Kyunghun (Sci Rep, 2020)
We investigated differences in cortical thickness between idiopathic normal-pressure hydrocephalus (INPH) patients and healthy controls. We also explored whether a relationship exists between cortical thinning and gait disturbance in INPH patients. Forty-nine INPH patients and 26 healthy controls were imaged with MRI, including 3-dimensional volumetric images, for automated surface-based cortical thickness analysis across the entire brain. Compared with age- and gender-matched healthy controls, unexpectedly, INPH patients showed statistically significant cortical thickening mainly in areas located in the high convexity of the frontal, parietal, and occipital regions. Additionally, cortical thinning mainly in temporal and orbitofrontal regions was observed in the INPH group relative to the control group. The Gait Status Scale (GSS) scores were negatively correlated with cortical thickness in the medial orbital part of the superior frontal gyrus, gyrus rectus, superior temporal gyrus, temporal pole, and insula. A distinctive pattern of cortical thickness changes was found in INPH patients. We cautiously suggest that cortical thickening in INPH can result from reactive gliosis. Further, our results support the hypothesis that cortical thinning in INPH can result from neuronal degeneration. In addition, cortical thinning can play an important role in gait disturbances in INPH patients.